Issues in the Management of VTE - Nierengarten, Mary Beth (MD Conference Express, 2014)
What are the long-term consequences for a patient after a blood clot, and how does this inform management of venous thromboembolism (VTE)? These article discusses the use and efficacy of novel anticoagulants, thrombolytics for pulmonary embolism, and the development of chronic thromboembolic pulmonary hypertension.